Foreign direct investment in Brazil: A positive perspective of the future. (31st October 2018) - Bernardi, Amanda; Floyd, David
Abstract: Brazil is a place for long‐term investments, but it is losing its attractiveness to the foreign market while factors such as location and ease of implementation of the business are the only determinants of the investor. Basic education, political stability, and fiscal reforms have been identified as areas having implications for policy making.